2015
DOI: 10.1538/expanim.14-0050
|View full text |Cite
|
Sign up to set email alerts
|

Vital signs monitoring during injectable and inhalant anesthesia in mice

Abstract: Selecting the appropriate anesthetic protocol for the individual animal is an essential part of laboratory animal experimentation. The present study compared the characteristics of four anesthetic protocols in mice, focusing on the vital signs. Thirty-two male ddY mice were divided into four groups and administered anesthesia as follows: pentobarbital sodium monoanaesthesia; ketamine and xylazine combined (K/X); medetomidine, midazolam, and butorphanol combined (M/M/B); and isoflurane. In each group, rectal te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
110
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(125 citation statements)
references
References 26 publications
9
110
0
4
Order By: Relevance
“…Although published documents reported that the effects of anesthesia on murine models of lung injury should be considered, the dosage (50 mg/ kg) we used is a relatively low dose in mice [33] and no pentobarbital-induced death was observed in the present study. The O 2 saturation (SPO 2 ) at this dose is approximately 90% at 35-40 min after anesthesia [34], which would not have a significant effect on ALI.…”
Section: Discussionmentioning
confidence: 93%
“…Although published documents reported that the effects of anesthesia on murine models of lung injury should be considered, the dosage (50 mg/ kg) we used is a relatively low dose in mice [33] and no pentobarbital-induced death was observed in the present study. The O 2 saturation (SPO 2 ) at this dose is approximately 90% at 35-40 min after anesthesia [34], which would not have a significant effect on ALI.…”
Section: Discussionmentioning
confidence: 93%
“…The most severe adverse effect of isoflurane is depression of respiratory rate, superior to that induced by ketamine/xylazine and pentobarbital; however, tidal volume seems to be better maintained during isoflurane anesthesia, accounting for relatively higher peripheral capillary oxygen saturation (SPO 2 ) compared with pentobarbital (78). …”
Section: Variables Affecting Cardiac Radionuclide Studies In Rodents:mentioning
confidence: 99%
“…Such effect was not observed after 20 h of fasting, suggesting that it might be related to transient fluctuations of glucose levels (64). Respiratory depression with reduction of SPO 2 is of most concern after administration of pentobarbital (78). …”
Section: Variables Affecting Cardiac Radionuclide Studies In Rodents:mentioning
confidence: 99%
See 1 more Smart Citation
“…In sedated mouse models, the heart rate is expected in the range 5 < f h < 10 Hz (300 to 600 bpm). 24,25 Thus, the minimum sampling rate required is f min ÂŒ 20 Hz. In spectral-domain OCT, each axial scan (A-scan) is acquired by a single spectrometer exposure at a rate f Ascan .…”
Section: Theorymentioning
confidence: 99%